Safety of prothrombin complex concentrates for rapid anticoagulation reversal of vitamin K antagonists - Dentali, Francesco; Marchesi, Chiara; Pierfranceschi, Matteo Giorgi; Crowther, Mark; Garcia, David; Hylek, Elaine; Witt, Daniel M.; Clark, Nathan P.; Squizzato, Alessandro; Imberti, Davide; Ageno, Walter (Thrombosis and Haemostasis, 2011)
Prothrombin complex concentrates (PCCs) are recommended as the treatment of choice in warfarin-related coagulopathy. However, the risk of thromboembolic complications associated with their use is not well defined. We performed a meta-analysis to estimate the rate of thromboembolic complications in patients receiving vitamin K antagonists (VKAs) treated with PCCs for bleeding or before urgent surgery. Medline and Embase databases were searched. Two reviewers performed study selection and extracted data independently. Studies providing data on incidence of thromboembolic complications in VKA-treated patients were eligible for the study. Weighted mean proportion of the rate of thromboembolic complications and the mortality rate were calculated. Twenty-seven studies (1,032 patients) were included. Seven studies used 3-factor, and 20 4-factor PCCs. Twelve patients had a thromboembolic complication (weighted mean 1.4%; 95% CI 0.8–2.1), of which two were fatal. The incidence of thromboembolic events was 1.8% (95% CI 1.0–3.0) in patients treated with 4-factor PCCs, and 0.7% (95% CI 0.0–2.4) in patients treated with 3-factor PCCs. Total mortality rate was 10.6% (95% CI 5.9–16.6). In conclusion, our results suggest there is a low but quantifiable risk of thromboembolism in VKA-treated patients receiving PCCs for anticoagulation reversal. These findings should be confirmed in randomised, controlled trials.
Keywords: Prothrombin complex concentrates; PCC; coumarins; thromboembolic complications; haemorrhage